Extreme environments as potential drivers of convergent evolution by exaptation: the Atacama Desert Coastal Range case - Azua-Bustos, Armando; González-Silva, Carlos; Arenas-Fajardo, Cristián; Vicuña, Rafael (Frontiers in Microbiology, 2012)
We have recently discovered a variety of unrelated phototrophic microorganisms (two microalgae and one cyanobacteria) in specialized terrestrial habitats at The Coastal Range of the Atacama Desert. Interestingly, morphological and molecular evidence suggest that these three species are all recent colonists that came from aquatic habitats. The first case is Cyanidiales inhabiting coastal caves. Cyanidiales are microalgae that are commonly found in warm acid springs, but have also been recently discovered as cave flora in Italy. The case is Dunaliella biofilms colonizing spider webs in coastal caves; Dunaliella are microalgae typically found in hypersaline habitats. The third case is Chroococcidiopsis, a genus of Cyanobacteria commonly found in deserts around the world that has also been described in warm springs. Thus, we show that the traits found in the closest ancestors of the aforementioned species (which inhabited other unrelated extreme environments) seem to be now useful for the described species in their current subaerial habitats, and may likely correspond to cases of exaptations. Altogether, the Coastal Range of the Atacama Desert may be considered as a place where key steps on the colonization of land by phototrophic organisms seem to be being repeated by convergent evolution of extant microalgae and Cyanobacteria.